2020
DOI: 10.5194/cp-16-799-2020
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between low-temperature fires, climate and vegetation during three late glacials and interglacials of the last 430 kyr in northeastern Siberia reconstructed from monosaccharide anhydrides in Lake El'gygytgyn sediments

Abstract: Abstract. Landscapes in high northern latitudes are assumed to be highly sensitive to future global change, but the rates and long-term trajectories of changes are rather uncertain. In the boreal zone, fires are an important factor in climate–vegetation interactions and biogeochemical cycles. Fire regimes are characterized by small, frequent, low-intensity fires within summergreen boreal forests dominated by larch, whereas evergreen boreal forests dominated by spruce and pine burn large areas less frequently b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
12
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 129 publications
(241 reference statements)
2
12
0
Order By: Relevance
“…A principal component analysis (PCA; package "stats"; R Core Team, 2020) was used to assess relationships among the various centred log-ratio (clr) transformed (package "compositions"; van den Boogaart et al, 2020) relative distributions of charcoal particle classes. To evaluate potential associations between charcoal accumulation and vegetation we applied correlation tests using Kendall's τ (package "psych"; Revelle, 2020) to clr-transformed relative distributions of pollen types and charcoal classes following Dietze et al (2020).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A principal component analysis (PCA; package "stats"; R Core Team, 2020) was used to assess relationships among the various centred log-ratio (clr) transformed (package "compositions"; van den Boogaart et al, 2020) relative distributions of charcoal particle classes. To evaluate potential associations between charcoal accumulation and vegetation we applied correlation tests using Kendall's τ (package "psych"; Revelle, 2020) to clr-transformed relative distributions of pollen types and charcoal classes following Dietze et al (2020).…”
Section: Methodsmentioning
confidence: 99%
“…The main fire regimes in the European and western Siberian evergreen boreal forest also differ markedly from those of its larch-dominated, deciduous counterpart in eastern Siberia. Many prevalent evergreen conifers (Pinus sibirica, Picea obovata, Abies sibirica) are commonly seen as fire avoiders and are more susceptible to crown fires 70 (Dietze et al, 2020;Isaev et al, 2010;Rogers et al, 2015). The predominant eastern Siberian larches (Larix gmelinii, L. cajanderi, L. sibirica), on the other hand, can resist fires with an insulating bark protecting the cambium from heat, while their deciduous and self-pruning nature restricts fires from reaching the crown (Wirth, 2005).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…When compared to the pastoralist societies that existed up to that point, anthropogenic influence on the fire regime likely increased at the end of phase 3 (ca. 1700 CE onwards) and throughout phase 4 after colonization and industrialization (Drobyshev et al, 2004). It has been shown that human livelihoods and the mentality towards fire use can often better explain shifts in fire regimes than population density alone (Bowman et al, 2011;Dietze et al, 2018).…”
Section: Human Activitymentioning
confidence: 99%
“…Levoglucosan may also be prone to post-depositional degradation, although the knowledge of its impact on levoglucosan concentrations over long time scales is limited (Suciu et al, 2019). Levoglucosan is detected in considerable concentrations in sediments dating back to 200 ka (Schreuder et al, 2019), 270 ka (Elias et al, 2001), and 430 ka (Dietze et al, 2020), suggesting its long lifetime in sedimentary environments after deposition, possibly related to the adsorption to biogenic particles proposed by Schreuder et al (2018). The postdepositional degradation of levoglucosan cannot be completely ruled out but is expected to have minor impact on the downcore variation in our record.…”
Section: Minor Effect Of Degradation On Levoglucosan and Lvg/(lvg + Pahs) Ratiomentioning
confidence: 99%